Management of Limited Interocclusal Distance with the Aid of a Modified Surgical Guide: A Clinical Report - Farideh Geramipanah; Leyla Sadighpour; Amirreza Hendi (Tehran University of Medical Sciences, 2017)
In completely edentulous patients, limited interarch distance can compromise conventional prosthetic fabrication. Bone reduction through various surgical procedures has been recommended to restore an acceptable interarch distance. In such circumstances, a surgical guide built on a mounted cast can be used to minimize and control the amount of bone reduction performed. In the present report, an innovative method of fabrication of surgical guide has been described.